Defining Sudden Infant Death and Sudden Intrauterine Unexpected Death Syndromes with Regard to Anatomo-Pathological Examination - Ottaviani, Giulia (Frontiers in Pediatrics, 2016)
Crib death, or sudden infant death syndrome (SIDS), is the most frequent form of death in the first year of life, striking one baby in every 1,700–2,000. Yet, despite advances in maternal–infant care, sudden intrauterine unexplained/unexpected death syndrome (SIUDS) has a sixfold to eightfold greater incidence than that of SIDS. Frequent congenital abnormalities, likely morphological substrates for SIDS–SIUDS, were detected, mainly represented by alterations of the cardiac conduction system, such as accessory pathways and abnormal resorptive degeneration, and hypoplasia/agenesis of the vital brainstem structures. On the basis of these considerations, the new common definition of the SIDS–SIUDS complex is “The sudden death of a fetus after the 25th gestational week or infant under one year of age which is unexpected by history and remains unexplained after a thorough case investigation, including examination of the death scene, performance of a general autopsy and examination of the fetal adnexa”. Therefore, given that the general autopsy does not disclose any cause of death, a more in-depth histopathological analysis of the cardiac conduction system and autonomic nervous system by specialized pathologists is necessary.